LITERASI INFORMASI KESEHATAN PADA FENOMENA DIAGNOSIS MANDIRI COVID-19 MELALUI SUMBERDAYA ONLINE - Muhammad Al Assad Rohimakumullah; Intan Primasari; Angling Dwi Wicaksono; Anindya Fatona (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
This phenomenon of self diagnose through online resources in the era of the covid-19 pandemic is something that is dangerous in the diagnosis process. Information literacy about health plays an important role in the process of self-diagnosis of this phenomenon. This study will discuss how the experience of health information literacy is for patients who self-diagnose through online resources in the era of the covid-19 pandemic. This study will use a qualitative method by integrating a phenomenological approach and the seven pillars of information literacy standards. The results of this study show that there are physical and psychological vulnerabilities, which have an impact on information neglect, the quality of health information that makes patients depressed, and corrective actions from expert informants and references. Keywords: health literacy information, online resources, phenomenology, self-diagnosis